Penggunaan Metode Bermain Kartu Soal Untuk Meningkatkan Kemampuan Siswa Dalam Mengerjakan Soal Cerita Pada Mata Pelajaran Matematika Bagi Siswa Kelas VI SD Negeri 22 Kepahiang Tahun Pelajaran 2020/2021 - Husin Husin (Journal Of Dehasen Educational Review, 2025)
Classroom action research aims descriptively to determine the effect of the question card playing method on improving the ability to work on story problems in class VI mathematics at SD Negeri 22 Kepahiang in 2020/2021. The hypothesis in this study is "The learning model using question cards is thought to be able to improve the ability of grade VI students of SD Negeri 22 Kepahiang in 2020/2021 in working on story problems in mathematics subjects." The subjects who were given the action were the sixth grade students of SD Negeri 22 Kepahiang in 2020/2021, totaling 14 students and divided into 4 groups. The form of action given is to use question cards that are used to write story questions then discussed by students in groups and then discussed together between teachers and students. To find out the increase in students' ability to work on story questions, a trial test was carried out twice and the results were analyzed. The results of the descriptive study showed that the trend of mathematics learning achievement of grade VI students of SD Negeri 22 Kepahiang was increasing, namely by obtaining an average score before taking action by 60 and after taking action I to 70 and in action II increasing to 84.3 thus means that there is an increase in learning outcomes of 24.3.